Markers of Macrovascular Complications in Pediatric Diabetes - Vinall, Phil (MD Conference Express, 2012)
Children with diabetes are at high risk for premature cardiovascular disease (CVD), which can lead to mortality later in life. Screening and treatment of modifiable risk factors in young patients with diabetes are important to decrease lifetime risk for CVD. This article discusses several noninvasive surrogate measures that would allow for the stratification of CVD risk, and he presented evidence for more aggressive treatment of patients at the highest risk for macrovascular disease in adulthood.